“Efecto de la fertilización nitrogenada en el cultivo de stevia (stevia rebaudiana bertoni) en la producción de materia seca bajo condiciones de San Martín” - Vera Peralta, Clayri Dianelly (2016)
This research conducted in 2013 at the lnstitute of Tropical Crops (ICT), Juan Bernito Experimental Station of the District of Shilcayo Band, located geographically to 06º 30' 07" south latitude and 76º 20' 09" west longitude with an altitude of 360 meters above sea level. The work was to evaluate the effect of nitrogen fertilization in the cultivation of stevia (Stevia rebaudiana Bertoni) in dry matter production, under conditions of San Martin. By applying urea in an area of 85.1 m2 with distancing 0.20 cm between plants, 50 cm between furrow, 1 m street between treatments and 1 m street between machining blocks in soil (beds); the application of fertilizar will be three applications in ayear, the first application to the two months after planting. The treatments were the TO (witness), T1 (30-00 -00), T2 (60-00 -00), T3 (90-00 -00) and T4 (120-00 -00), the evaluations were conducted every 14 days, eight plants for each treatment. We use the completely randomized design with five treatments and three blocks. The evaluations recorded and analyzed statistically were the following: plant height, number of tillers/bushes, number of leaves per plant, weight of leaves plus branches, performance of dry leaf, number of harvests and Brix. The statistical analysis enabled us to conclude that the treatment T 4 reportad the highest averages in number of leaves per plant, plant height, and tillers/bushes, weight of leaves plus branches and performance of dry leaf.